DESCRIPTIVE STUDIES OF KIDNEY FAILURE IN BANGAH VILLAGE, GEDANGAN SUB-DISTRICT - Afifah, Yeni Nur (Global Ten Public Health and Nursing Journal, 2024)
Abstract Kidney failure is the inability of the kidneys to function adequately for the body's needs (must be assisted by dialysis or transplantation. Generally, patients are not aware that they are suffering from terminal kidney failure because this disease progresses gradually and takes years as the patient's kidney function declines. There are two general terms for Kidney Failure, namely, Acute Kidney Failure and Chronic Kidney Failure. According to 2018 World Health Organization (WHO) data, around 71% of deaths in the world are caused by Non-Communicable Diseases (PTM).In 2020, it is estimated that the death rate this will increase to 73%.The results of basic health research (Riskesdas) 2013, stated that Chronic Kidney Failure (CKD) increased from 20% to 38% in 2018. The problem is that the authors are interested in conducting research entitled "Descriptive Study of Kidney Failure RT 08 RW 02 Bangah Village, Gedanga District. Based on the background above, it can be seen that the incidence of Kidney Failure in Sidoarjo is increasing and high in Bangah Village. So the problem is that the authors are interested in conducting research entitled "Descriptive Study of Kidney Failure Disease RT 08 RW 02 Bangah Village, Gedangan District. This study aims to find out about descriptive studies of kidney failure. The type of research used is descriptive analytic with a cross sectional approach. The sampling technique in this study is total sampling. Data collection was carried out by filling out a questionnaire prepared by the researcher. The results of the study revealed that of the 40 respondents in Bangah village, it was shown that the majority. Enough knowledge about kidney failure with the criteria of 16 respondents (40%). Keywords: Knowledge, Disease, Kidney Failure.